Karakteristik Bubuk Buah Salak Gula Pasir (Salacca Zalacca Var. Amboinensis) Pada Perlakuan Lama Dan Suhu Blansir - Wardana, Made Kusuma; Wrastiati, Luh Putu; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Salak is one of the tropical plants that is often found in almost all provinces in Indonesia. This fruit has a high water content of 78%, so further processing is needed and one alternative to increase the economic value of salak fruit is to make it into salak fruit powder. This study aims to determine the effect of blanching temperature and blanching time on the characteristics of granulated sugar salak fruit powder (Salacca Zalacca var. Amboinensis) and to determine the best blanching temperature and blanching time treatment to produce granulated sugar salak powder. This study used a factorial randomized block design with 2-factor experiments. The first factor is the blanching temperature consisting of 3 levels, namely 70, 80, 90○C. The second factor is the blanching time consisting of 3 levels, namely 1, 3, 5 minutes. Each treatment was carried out 2 times and 18 experimental units were obtained. The data obtained were analyzed by ANOVA analysis. if the results obtained have a significant effect on the observed variables, it will be continued with the Tukey test. The results of the study showed that the effect was not significant or not real (P>0.05) on the average value of water content and total phenol. While in the vitamin C test, the level of brightness (L*), redness (a*), yellowness (b*) obtained significant or real results (P<0.05). Blanching time one minutes and blanching temperature 90○C is the best treatment.